Productive characterization and socioeconomic of the sector rural of the province of Pamplona - Gualdrón Guerrero, Carlos Andrés; Jaimes Gauta, Gendler Alexander; Hernández Pérez, Nathalie (2024)
Pamplona is one of the 40 municipalities of the department of Norte de Santander and belongs to the south-western region of the Department, along with other municipalities such as Pamplonita, Chitagá, Silos, Cácota and Mutiscua. Pamplona's economy is based on agricultural production and manufacturing, is recognized for its religiosity and its celebration of Holy Week, which led it to be declared cultural heritage intangible heritage of the Nation in 2013. It has museums that house works of religious art and colonial painting. Due to its characteristics, there is interest in investigating the agricultural productive potential of Pamplona through the socioeconomic characterization of the municipality and the development conditions in rural areas with the objective of identifying strengths and weaknesses to propose sustainable solutions that promote economic growth and regional development. The research was of a descriptive type in which a compilation was made of information from primary and secondary sources. They analyzed the technical conditions used by farmers, level and quality of life among people in rural areas and the use of natural resources that provide relevant information for execution of public policies.
Keywords: Pamplona; Municipality; Rural development; Development; Socioeconomic analysis; Natural resources